2018
DOI: 10.1037/tra0000238
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial to dismantle exposure, relaxation, and rescripting therapy (ERRT) for trauma-related nightmares.

Abstract: Findings indicate that ERRT with and without nightmare exposure and rescripting can significantly alleviate nightmares and related distress. The addition of nightmare exposure and rescription did not contribute incrementally to outcomes in this sample. It is possible that the dose of exposure was not sufficient to result in group differences or that the treatment components included in both conditions (i.e., psychoeducation about trauma, nightmares, and sleep; sleep habit modification; and relaxation training)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
49
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 56 publications
5
49
0
1
Order By: Relevance
“…Furthermore, it has been argued that exposure to nightmare content is not a necessary treatment component, as IRT is effective with minimal exposure (Krakow, Hollifield et al., ). However, some studies suggest that an intervention of relaxation training and sleep habit modification does not perform worse than the full IRT protocol including exposure and rescripting (Miller & Dipalato, ; Pruiksma, Cranston, Rhudy, Micol, & Davis, ). The literature thus remains unclear and sometimes conflicting.…”
Section: The Treatment Of Nightmare Disordermentioning
confidence: 99%
“…Furthermore, it has been argued that exposure to nightmare content is not a necessary treatment component, as IRT is effective with minimal exposure (Krakow, Hollifield et al., ). However, some studies suggest that an intervention of relaxation training and sleep habit modification does not perform worse than the full IRT protocol including exposure and rescripting (Miller & Dipalato, ; Pruiksma, Cranston, Rhudy, Micol, & Davis, ). The literature thus remains unclear and sometimes conflicting.…”
Section: The Treatment Of Nightmare Disordermentioning
confidence: 99%
“…Both EX and NEX consisted of three sessions. For the latter study, Pruiksma et al (2016) found no differences between the EX and NEX groups, so both groups were included in the present study. Treatments included the following components: psychoeducation about trauma, sleep, and nightmares, sleep modification including stimulus control, and relaxation procedures.…”
mentioning
confidence: 88%
“…(For additional information regarding participant flow, see Davis et al, 2011 andPruiksma et al, 2016. Exclusion criteria included psychosis, cognitive impairment, active suicidal intent, current or past manic episodes, and untreated drug or alcohol abuse or dependence in the past 6 months.…”
mentioning
confidence: 99%
See 2 more Smart Citations